ANALISIS KESULITAN PEMECAHAN MASALAH MENYELESAIKAN SOAL CERITA DITINJAU TEORI POLYA PADA MATERI OPERASI HITUNG BILANGAN CACAH SISWA KELAS V SDN 1 PANGENREJO - Syifa Agnessya; Rintis Rizkia Pangestika; Arum Ratnaningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to 1) Describe the problemsolving difficulties of solving story problems in terms of Polya's theory on the operation material of small numbers of grade V students. 2) Knowing the factors that cause problem solving difficulties in solving story problems in terms of Polya's theory on the material for the operation of whole numbers of grade V students. This type of research is qualitative descriptive. Data collection techniques are observation, interviews, documentation, and data logging cards. The research instruments used data recording cards, observations and interviews. Data analysis uses data collection, data reduction, data presentation, and conclusion or verification. The results of descriptive analysis showed that students with difficulties in addition and division arithmetic operations according to Polya's theory had difficulty understanding the problem, making plans, implementing plans and re-examining answers. Students with difficulties in multiplication and subtraction arithmetic operations according to Polya's theory, have difficulty implementing the plan, students have not fulfilled one of the conditions for understanding the problem, and re-examining the answer. The factors that cause students' problemsolving difficulties in solving story problems on the material for counting operations of numerical numbers are, internal factors, learning attitudes and motivation to learn Mathematics. External factors, the teacher's ability to use media, classroom atmosphere, parental or family assistance, and community environment.